Antioxidant, Antimicrobial Activity of Olive Leaf Extract and Oleuropein, Their Possibilities Usage in Foods - Mustafa Bayram; Semra Topuz; Cemal Kaya (Turkish Journal of Agriculture: Food Science and Technology)
Olive leaves which is one of the by-products of olive tree cultivation and olive processing industry, have been used in traditional folk medicine for centuries. In recent studies, it has been determined that olive leaf has many bioactivities and these effects have been associated with high phenolic compound content. The most dominant phenolic compound of olive leaf is oleuropein, which is the heterosidic ester of elenolic acid and 3,4-dihydroxyphenylethanol. Therefore, some studies have been carried out for extracting high value added compounds from olive leaves in recent years. Antioxidant and antimicrobial activities of crude phenolic extract and oleuropein have been investigated. Moreover, some studies have been carried out to increase the possibility of using olive leaf extract and oleuropein in food industry due to increasing suspicion of side effects and toxicity of synthetic food preservatives. In this review, it was aimed to investigate phenolic compounds of olive leaf extract, phenolic compound extraction from olive leaf as well as antioxidant, antimicrobial activity of olive leaf extract and oleuropein and possibilities of use in foods.